Encoding Control, Decoding Resistance: State Power, Digital Media, and Identity Negotiation in Contemporary China - Bambang Dwi Waluyo; Astri Puspasari; Kausar Ali (MD Research Center, 2026)
China’s rapid digital transformation has created a media ecosystem where technological innovation is closely intertwined with state governance and ideological regulation. This study examines how digital media, state power, and audience agency interact to shape identity construction in China’s digital public sphere. Employing a qualitative literature review with thematic analysis, the research synthesizes recent scholarship on digital governance, platform regulation, and audience reception. The analysis draws on Stuart Hall’s Encoding/Decoding model, Michel Foucault’s concept of governmentality, and Antonio Gramsci’s theory of hegemony. The findings reveal that China’s digital infrastructure simultaneously expands communication while reinforcing state oversight through algorithms, platform governance, and content moderation. Audience responses are not homogeneous but include hegemonic, negotiated, and oppositional readings shaped by social and cultural contexts. The study concludes that China’s digital media environment is a dynamic arena where state institutions, platforms, and users continuously negotiate meaning and identity, extending debates on digital authoritarianism, media power, and political communication.